Culturally Aligned Aged-Care Services: Addressing Needs and Barriers in General Santos City, Philippines - Dec Airo Mari Ausan (Open Access Indonesia Journal of Social Sciences, 2024)
The aging population in General Santos City, Philippines, presents unique challenges in accessing and delivering appropriate aged-care services. This study aimed to identify the preferred aged-care services among the elderly population in General Santos City, considering their cultural values and needs, and to propose a framework for developing culturally aligned aged-care support services for the elderly in General Santos City. A mixed-methods research design was employed, combining qualitative and quantitative approaches. In-depth interviews with 30 elderly residents, community leaders, and caregivers were conducted to gather information on their preferences and needs for aged-care services. Thematic analysis was used to analyze the qualitative data. A survey questionnaire was also used to collect quantitative data on the demographic characteristics of the respondents and their perceptions of the importance of various aged-care services. The findings indicated healthcare services, home-based care, and social support as essential components of aged-care services. Barriers to accessing services included availability, affordability, accessibility, and awareness. Culturally sensitive, family-centered, and community-based care was preferred. The study also found that the elderly in General Santos City have a strong preference for culturally aligned aged-care services that are family-centered and community-based. They also expressed a need for affordable and accessible healthcare services, as well as social support services to reduce isolation and promote mental well-being. In conclusion, the study highlights the need for a holistic aged-care approach that integrates healthcare services, home-based care, and social support, while considering cultural values and addressing barriers to access. The proposed aged-care services emphasize culturally sensitive, family-centered, and community-based models of care. These models should be tailored to the specific needs of the elderly population in General Santos City, taking into account their cultural values and beliefs.